Perivascular Adipose Tissue as a Relevant Fat Depot for Cardiovascular Risk in Obesity - Costa, Rafael M.; Neves, Karla B.; Tostes, Rita C.; Lobato, Núbia S. (Frontiers in Physiology, 2018)
Obesity is associated with increased risk of premature death, morbidity and mortality from several cardiovascular diseases, including stroke, coronary heart disease, myocardial infarction and congestive heart failure. However, this is not a straightforward relationship. Although several studies have substantiated that obesity confers an independent and additive risk of all-cause and cardiovascular death, there is significant variability in these associations, with some lean individuals developing diseases and others remaining healthy despite severe obesity, the so-called metabolically healthy obese. Part of this variability has been attributed to the heterogeneity in both the distribution of body fat and the intrinsic properties of adipose tissue depots, including developmental origin, adipogenic and proliferative capacity, glucose and lipid metabolism, hormonal control, thermogenic ability and vascularization. In obesity, these depot-specific differences translate into specific fat distribution patterns, which are closely associated with differential cardiometabolic risks. The adventitial fat layer, also known as perivascular adipose tissue (PVAT), is of major importance. Similar to the visceral adipose tissue, PVAT has a pathophysiological role in cardiovascular diseases. PVAT influences vascular homeostasis by releasing numerous vasoactive factors, cytokines and adipokines, which can readily target the underlying smooth muscle cell layers, regulating the vascular tone, distribution of blood flow, as well as angiogenesis, inflammatory processes and redox status. In this review, we summarize the current knowledge and discuss the role of PVAT within the scope of adipose tissue as a major contributing factor to obesity-associated cardiovascular risk. Relevant clinical studies documenting the relationship between PVAT dysfunction and cardiovascular disease with a focus on potential mechanisms by which PVAT contributes to obesity-related cardiovascular diseases are pointed out.